2015
DOI: 10.1007/s10571-015-0267-6
|View full text |Cite
|
Sign up to set email alerts
|

Expression of BDNF and TrkB Phosphorylation in the Rat Frontal Cortex During Morphine Withdrawal are NO Dependent

Abstract: Nitric oxide (NO) mediates pharmacological effects of opiates including dependence and abstinence. Modulation of NO synthesis during the induction phase of morphine dependence affects manifestations of morphine withdrawal syndrome, though little is known about mechanisms underlying this phenomenon. Neurotrophic and growth factors are involved in neuronal adaptation during opiate dependence. NO-dependent modulation of morphine dependence may be mediated by changes in expression and activity of neurotrophic and/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…NOS is a key factor which produces endogenous NO that widely exists in gastrointestinal tissues and plays an important role in modulating gastrointestinal movements. The increasing level of NO has been shown to be involved in colonic motility disorders of constipation ( 33 ). The downregulation of NOS can reduce the production of NO, which is a feasible way to relieve constipation ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…NOS is a key factor which produces endogenous NO that widely exists in gastrointestinal tissues and plays an important role in modulating gastrointestinal movements. The increasing level of NO has been shown to be involved in colonic motility disorders of constipation ( 33 ). The downregulation of NOS can reduce the production of NO, which is a feasible way to relieve constipation ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide (NO) signaling can also regulate the expression of BDNF, GDNF and their receptors in different brain regions of morphine-dependent rats after spontaneous morphine withdrawal (Peregud et al, 2015). In these experiments morphine withdrawal was accompanied by an increased expression of BDNF mRNA in the frontal cortex, hippocampus, and midbrain, while the mRNA levels of the BDNF receptor TrkB were increased only in the frontal cortex.…”
Section: Gdnf and Bdnf In Drug Seeking Behavior In Laboratory Animalsmentioning
confidence: 99%
“…In these experiments morphine withdrawal was accompanied by an increased expression of BDNF mRNA in the frontal cortex, hippocampus, and midbrain, while the mRNA levels of the BDNF receptor TrkB were increased only in the frontal cortex. Interestingly, the authors showed that administration of the NO synthase inhibitor L-N G -nitroarginine methyl ester (L-NAME) during morphine intoxication prevented the increase in BDNF and TrkB mRNA expression, suggesting that NO signaling during the development of morphine dependence can modulate the BDNF/TrkB pathway (Peregud et al, 2015). …”
Section: Gdnf and Bdnf In Drug Seeking Behavior In Laboratory Animalsmentioning
confidence: 99%
“…This indicates that the GM is connected to the CNS through BDNF. Morphine use has been shown to increase the expression of BDNF and NTRK2 in the brain ( Numan et al, 1998 ; Akbarian et al, 2002 ; Bolanos and Nestler, 2004 ; Vargas-Perez et al, 2009 ; Koo et al, 2012 ; Mashayekhi et al, 2012 ; Peregud et al, 2016 ; Naghshvarian et al, 2017 ). In our study, the mRNA expression of bndf and ntrk2 in zebrafish increased significantly after morphine administration, while isorhynchophylline reversed this change.…”
Section: Discussionmentioning
confidence: 99%